Differences Between Phenolic Content and Antioxidant Capacity of Quillay Chilean Honeys and Their Separated Phenolic Extracts [Diferencia Entre el Contenido de Compuestos Fenólicos y la Capacidad Antioxidante de Mieles Chilenas de Quillay y Sus Extractos Fenólicos Separados] - Lissi-Gervaso, E (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2017)
The differences between entire quillay honeys and their separated phenolic extracts in terms of phenolic content, flavonoid content and scavenging activity assessed through an Oxygen Radicals Absorbance Capacity (ORAC) assay were determined. The separated phenolic extracts of honey were obtained using Amberlite XAD-2, which is the procedure most used in analytical methods, biological assays and functional food development. The results showed that phenolic and flavonoid contents and antioxidant activity were higher in entire honeys than in their separated phenolic extracts. The recovery of phenolic acids and flavonoids was variable and depended upon the method employed. The application of polyvinylpolypyrrolidone (PVPP), a water insoluble synthetic polymer, in the separated extracts indicated an important influence of non-phenolic reducing compounds in the polyphenolic content measured by the Folin– Ciocalteu method. This showed the elution with methanol of these compounds together with phenolic compounds using an Amberlite XAD-2 column. The antioxidant capacity assessed through ORAC-FL and ORAC-PGR was less influenced by the interference of non-phenolic compounds than by that of total phenolic and flavonoid contents. © 2017, Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal. All rights reserved.